BUSINESS MODEL CANVAS AND FINANCIAL FEASIBILITY ANALYSIS OF PUPUKIN!: A MULTIFUNCTIONAL SLOW-RELEASE ORGANIC FERTILIZER FOR URBAN FARMING - Muhammad Yasyfa Kusumadinata; Dira Purwasih; Rizqia Nadira Ronaldo; Prili Alisha; Stanislaus Adhi Pramudya; Vira Kusuma Dewi (Syarif Hidayatullah State Islamic University Jakarta, 2026)
Urban agriculture has been increasingly developed in response to the growing conversion of agricultural land into non-agricultural areas in urban regions. However, urban agriculture activities still face several challenges, particularly practical, efficient, and environmentally friendly fertilization practices. Pupukin! is an innovative, multifunctional slow-release organic fertilizer developed by utilizing organic waste materials such as banana corms, shrimp shells, and neem leaves as the main raw materials. This study aims to analyze the business model and financial feasibility of Pupukin! fertilizer business in supporting urban agriculture activities. The study employed a quantitative approach using the Business Model Canvas (BMC) to describe the business structure, as well as financial feasibility analysis, including production cost calculation, profit analysis, Revenue Cost Ratio (R/C Ratio), Payback Period (PP), and Return on Investment (ROI). The results indicate that the Pupukin! business model offers a key value proposition in multifunctional organic fertilizer that is practical, environmentally friendly, and efficient to use, making it suitable for urban agriculture practitioners. Financial analysis shows that the Pupukin! business is economically feasible, indicated by an R/C Ratio of 1.48. Furthermore, the business demonstrates a favorable investment return with an ROI of 48% and a relatively short Payback Period. These findings suggest that the Pupukin! fertilizer business has strong potential to be further developed as a sustainable agricultural innovation that supports the advancement of urban agriculture.